Attitudes of business administration students towards corporate social responsibility and business ethics - López Navarro, Miguel Ángel; Segarra Ciprés, Mercedes (Revista Complutense de Educación, 2012)
The responsible management and ethical values should be reflected in the field of education, especially in studies of business administration. From a sample of university business students, this paper examines their attitudes to responsible and ethical behavior in organizations. The results show that students, in their conception of what a well-run company, are close to a stakeholders’ perspective. There are also differences between the perceptions of the current and ideal ethical climate. In addition, differences based on gender, but not according to the academic year, are observed which indicates that the education received does not significantly affect the perceptions of students in the topics addressed.